(untitled) (Annals of Medical Research, 2021)
Primary renal osteosarcoma is an extremely rare tumor. There are only 21 cases reported in the literature. Although surgery, polychemotherapy and radiotherapy are the options of treatment, yet there is no optimal treatment of choice settled. Despite all treatment modalities, the tumor has an aggressive clinical course and ominous prognosis and survival of the patients reported in the literatur varies between 8-22 months. Herein we present an incidental primary renal osteosarcoma, existing synchronously with xanthogranulomatous pyelonephritis, diagnosed in a simple nephrectomy material performed for non-functional stone kidney. This is the first case in the literature exhibiting the presence of primary renal osteosarcoma synchronously with xanthogranulomatous pyelonephritis and urolithiasis.